2017
DOI: 10.1016/j.wneu.2017.04.111
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Obliteration Rate of Intracranial Aneurysms Treated with a Single Pipeline Embolization Device

Abstract: Objective To evaluate the clinical and angiographic outcomes of intracranial aneurysm treatment using a single Pipeline Embolization Device (PED), and to evaluate the factors affecting aneurysm obliteration rate. Methods The demographic characteristics and anatomical features of 58 aneurysms in 47 patients treated with a single Pipeline embolization device were reviewed retrospectively. All aneurysms treated with one PED at a single center, and with follow-up angiograms of at least six months were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
0
17
2
1
Order By: Relevance
“…34 In the present study, the mean aneurysm size was larger in the ICO group than in the CO group; however, although significant in univariate analysis, this difference was not significant according to multivariate regression analysis. Numerous other studies of FDs have shown a tendency towards decreasing occlusion rates with increasing aneurysm size; 30,39,40 however, in most series, this tendency has not been statistically significant, as was the case in the present study. Large aneurysms take longer to thrombose and may have complex flow patterns as a result of pulsatile flow, resulting in coil changes.…”
Section: Discussioncontrasting
confidence: 73%
“…34 In the present study, the mean aneurysm size was larger in the ICO group than in the CO group; however, although significant in univariate analysis, this difference was not significant according to multivariate regression analysis. Numerous other studies of FDs have shown a tendency towards decreasing occlusion rates with increasing aneurysm size; 30,39,40 however, in most series, this tendency has not been statistically significant, as was the case in the present study. Large aneurysms take longer to thrombose and may have complex flow patterns as a result of pulsatile flow, resulting in coil changes.…”
Section: Discussioncontrasting
confidence: 73%
“…The presence of incorporated artery increases difficulties in endovascular treatment of the aneurysm; flow diverters provided a solution for those aneurysms [31]; we identified that incorporated vessels from the aneurysmal sac/neck is an independent predictor of incomplete aneurysm occlusion, the same announced in many studies [14,22,[32][33][34][35]. It is explained by pressure gradient kept by incorporated branch toward the aneurysm that reduced the flow diversion effect of the stent and in PCOM aneurysm theoretical explanation by retrograde filling of the sac via the posterior circulation resulting in residual aneurysm filling after treatment [22].…”
Section: Discussionmentioning
confidence: 55%
“…A lager aneurysmal size is associated with low occlusion rate the same realized in many studies [9,27,32,34,36,37]. Fetal origin PCOM artery almost always associated with failure of aneurysm occlusion [14][15][16][17]; it explains by high demand flow in largecaliber fetal PCOM artery keep the flow to it and disrupt the flow diversion effect.…”
Section: Discussionmentioning
confidence: 60%
“…8 Relatively limited data show that a single device results in complete or near-complete occlusion of most aneurysms, including those at bifurcations, without delayed complications or mortality. 9,10 A second-generation version, the Pipeline Flex, was approved in Europe in 2014 and the United States in 2015. While the device itself is identical to the original, the delivery system was enhanced to improve device deployment and provide additional safety by incorporating a resheathing feature (Fig 1 and On-line Table 1).…”
Section: Conventional Braided Mesh Devicesmentioning
confidence: 99%